Analisa Balok Tinggi Beton Bertulang Dengan Menggunakan Metode Strut and Tie Model (Studi Kasus Balok Tinggi Dengan Beban Merata) - Sitompul, Iskandar Romey; Munir, Misbakhul; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Strut-and-tie models (model fighters and binder) is derived from the truss analogy models. Concrete structures planning usually carried out under the assumption of Bernouli and Navier sectional analysis due to the bending moment. Expressed deep beam when the beam span to height ratio of less than five .One alternative approach to address the structural elements such as deep beam approach is to use a strut-and-tie models, namely by dividing the structure in region B (Bernouli) and D (Distrub) and describe the flow of force (load Plath) as the force transfer occurs reinforced concrete structures due to cracks conditions caused by forced, the parameters of the strut-and-Tie Model (STM) is press rod (strut), pull rods (tie) and points stains (stains zone) as a meeting area. The purpose of this thesis is to analyze the correlation among reinforcing volume to the quality of concrete, steel quality, and variation about long-span the deep beam with the conventional method and the method of Strut-and-tie-models (STM) based on ACI is verified by the Program Computer-Aided-Strut -and-Tie (CAST) The results of the analysis of the deep beam with a distributed load at the end of the assignment of conventional method is more efficient than the STM method for long span for spans of 2.5 and 3.0 m to 4.5 STM method is more efficient than conventional methods. This thesis also explain about high concrete reinforcing design manually base on conventional and strut and tie model (STM) in spite of use program computer-aided-strtu-and tie (CAST) In this study also obtain the correlation among the span length (L), the quality of concrete (f'c), the quality of the steel (fy) and the load evenly to the reinforcement ratio, the addition of span length to enlarge the reinforcement ratio, the addition can reduce the quality of the steel reinforcement ratio, and additional load can increase the reinforcement ratioKeyword: Deep beam, distributed load, reinforce volume, strut-and-tie model, concrete.